SARS-CoV-2 vaccination and uveitis: Are they linked?. (September 2022) - Waseem, Summaiyya; Ahmed, Syed Hassan; Fatima, Sharmeen; Shaikh, Taha Gul; Ahmed, Jawad
Abstract: In 2019, the discovery of a new strain of Coronavirus, later referred to as SARS-CoV2 took the world by storm, leading to a pandemic and shutting down all global activities. Several measures were taken adequately to combat the viral havoc, including developing numerous vaccines. All the vaccines currently available for the general population went through rigorous screenings and trials to ensure maximum safety and were only approved after that. However, once they were rolled out in the markets and administered to the population, some adverse reactions were reported, one of which included uveitis. It is an ocular inflammatory condition of the uveal tract, choroid, or iris. If untreated, it can lead to severe consequences, including blindness. It is further divided into four categories based on its anatomical location. Despite the rare incidence of uveitis following COVID-19 vaccination, it may contribute to vaccine hesitancy; hence addressing and digging into the pathophysiological cause is crucial. This study evaluates all the pathophysiological and demographical links between COVID-19 vaccination and uveitis, suggesting appropriate management plans. Highlights: The phenomenon of vaccine associated uveitis has been previously reported with several vaccines. The reporting of uveitis following COVID-19 vaccinations might contribute to vaccine hesitancy. Past medical history and certain demographic conditions might dispose some people to developing uveitis. Corticosteroids were the initial drug of choice for many cases. Large scale studies are needed to reach a decisive conclusion.